2020
DOI: 10.7150/jca.46978
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in folate-metabolizing genes associated with gastric cancer prognosis in northwest China subjects

Abstract: Influence of folate metabolism has long been studied in cancer and copies evidences have suggested that the key genes involved were correlated with GC risk and prognosis. However, their genetically association and contribution for GC prognosis are still elusive. To evaluate the effect of folate metabolism related genes polymorphisms on the prognosis of gastric cancer (GC), the genotype of seven single nucleotide polymorphisms (SNPs) of three genes were selected and genotyped in a cohort of 664 GC patients, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Researchers have indicated that high riboflavin consumption significantly decreases the risk of GC in TC and TT carriers compared with that in CC carriers, 8 , 21 and it was reported that TT or CT/TT genotypes were significantly associated with poorer overall survival. 10 This provided a clue that riboflavin consumption may improve patient survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have indicated that high riboflavin consumption significantly decreases the risk of GC in TC and TT carriers compared with that in CC carriers, 8 , 21 and it was reported that TT or CT/TT genotypes were significantly associated with poorer overall survival. 10 This provided a clue that riboflavin consumption may improve patient survival.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Among these polymorphisms, CT/TT or TT genotypes of the single nucleotide polymorphism rs1532268 in the MTRR gene coding region are significantly associated with a poorer overall survival compared with the CC genotype. 10 Several studies have evaluated the relationship between the risk of GC and the rs1532268 polyporphism, 8 , 9 , 11 13 but the results have been inconsistent. Thus, we conducted this meta-analysis to assess the effect of the rs1532268 polymorphism on GC susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“… 38 Although many studies have shown that MTHFR C677T polymorphism was associated with gastrointestinal cancer, the specific relationship was not clear. 18 , 38 , 39 We speculated that the specificity of MTFHR C677T polymorphism for gastrointestinal cancer during H.pylori infection might be related to the site of cancer origin. 19 , 40 The previous studies have reported that there was association between MTHFR C677T polymorphism and gastric cancer in Chongqing, and CT and TT genotypes were protective factors for gastric cardia cancer, and TT genotype was a risk factor for gastric body cancer.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the overexpression of Metase significantly promotes apoptosis and autophagy, thereby inhibiting gastric cancer [40,45,46]. Additionally, Met can exert an impact on the development of gastric cancer by influencing the survival of Helicobacter pylori [47][48][49][50]. It has been shown that Met enhances the efficacy of the chemotherapeutic drugs 5-fluorouracil and Cisplatin [47,[51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Met can exert an impact on the development of gastric cancer by influencing the survival of Helicobacter pylori [47][48][49][50]. It has been shown that Met enhances the efficacy of the chemotherapeutic drugs 5-fluorouracil and Cisplatin [47,[51][52][53]. The objective of this review is to analyze the role and mechanism of Met in the development of gastric cancer and to consider its potential implications in the treatment of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%